UTILIZATION OF TEA WASTE COMPOST ENRICHED MICROBES TO ENHANCE SOIL HEALTH AND TEA PLANT SUSTAINABILITY - Restu Wulansari; Elia Laila Rizqiyah; Erdiansyah Rezamela; Iftita Fitri (Gunung Djati Conference Series, 2026)
Tea plantations increasingly face challenges related to declining soil fertility, excessive reliance on inorganic fertilizers, and the accumulation of agro-industrial residues. This study evaluated the utilization of tea waste as a feedstock for bio-enriched compost and its effectiveness in improving soil quality and tea plant health in tea plantations of North Sumatra, Indonesia. Tea waste was composted for 45-60 days using microbial activators and subsequently enriched with beneficial microorganisms. A field efficacy trial was conducted using a factorial randomized block design with two factors: tea waste compost doses (0–4000 kg ha⁻¹ year⁻¹) and inorganic fertilizer levels (0–100% of the recommended rate). Observed parameters included tea shoot productivity and shoot ratio (plant health). The best response was achieved with the application of 1000 kg ha⁻¹ tea waste compost combined with 60% of the recommended inorganic fertilizer dose, resulting in an average 28% increase in shoot yield compared with the control. This treatment also improved peko shoot quality and enhanced production stability during dry periods. Increased soil organic matter, improved water retention, and greater microbial activity were identified as key mechanisms underlying these benefits. These findings demonstrate that tea waste compost represents a viable strategy for circular waste management and sustainable nutrient optimization in tea plantation systems, contributing to long-term soil health and resilient tea production.